A fuzzy cognitive map model for estimating the repercussions of Greek PSI on Cypriot Bank branches in Greece - Papaioannou, Maria C.; Neocleous, Costas; Schizas, Christos N. (My University, 2013)
Recently, Greece experienced a financial crisis unprecedented in its modern history. In May of 2010 Greece signed a bailout memorandum with Troika (a tripartite committee constituted by the European Central Bank, the European Commission and the International Monetary Fund). In February of 2012, they proceeded to a second bailout package along with a debt restructuring deal that included a private sector involvement (PSI). The overall loss, for the private investors, was equivalent to around 75%. Due to the strong economic ties between Greece and Cyprus, PSI had a substantial impact on the Cypriot economy. A fuzzy cognitive map (FCM) system has been developed and used to study the repercussions of the Greek PSI on the economic dynamics of Cyprus and more specifically on the probability of cutting off the Cypriot Bank branches that operate in Greece. The system allows one to observe how a change on some parameters can affect the stability of the rest of the parameters. Different promising scenarios were implemented, scaling the percentage of PSI from 0% to 80%.
Keywords: Fuzzy cognitive maps; Private sector involvement; Intelligent systems